The Finnish paradox: The curious absence of high-growth entrepreneurship in Finland - Erkko Autio (The Research Institute of the Finnish Economy (ETLA), 2009)
This paper looks at how well Finland performs in high growth entrepreneurship and uses data from the Global Entrepreneurship monitor to benchmark Finland against other European countries. It is found that Finland's prevalence rate of high growth entrepreneurial activity lags significantly behind most of its European and all of its Scandinavian peers. That this weak performance in high-growth entrepreneurship goes hand in hand with Finland being a world leader in per capita investment in R&D may be described as a paradox. The reasons underlying the underperformance of Finland remain however unclear. At this point, explanations should be sought in culture, industrial traditions and systemic experience in high growth entrepreneurship.
Keywords: D21; L25; M13; O12; O40; 330; Firm growth; high growth firms; gazelles; Unternehmenswachstum; Forschungskosten; Vergleich; Finnland; EU-Staaten